Analisa Unjuk Kerja Internal Combustion Engine Tipe T113d Terhadap Emisi Gas Buang - Suyatno Suyatno; Helen Riupassa; Marthina Mini (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the performance of the Internal Combustion Engine Type T113D on carbon monoxide (CO) and hydrocarbon (HC) exhaust emissions, engine efficiency and rotation, to obtain efficient CO and HC. The research process was carried out by: testing rotation variations of motor power, torque, thermal efficiency, average effective direct fuel consumption, carbon monoxide and hydrocarbons. The research results showed that at 1000 rpm the highest CO was 10.00% and the lowest CO at 3000 rpm was 8.59%. What then influences the increase and decrease in CO is the reduction in fuel and air which is less homogeneous or does not burn completely in the combustion chamber. So it makes CO become high. High carbon monoxide is influenced by a poor mixture of air and fuel so that it can affect combustion in the combustion chamber, causing low engine speed. The lower the rotation, the higher the hydrocarbons (HC), this is because the mixture of air and fuel is less homogeneous which can affect the level of hydrocarbons.